Islamic Education Perspective of Mahmud Yunus - Ilham Abdul Jalil (STIT Attaqwa, 2024)
The thinking of Islamic education in the perspective of Mahmud Yunus is a holistic and innovative approach that emphasizes the integration between Islamic teachings and modern knowledge, character building, inclusivity, and the use of participating teaching methods. The contribution of Mahmud Yunus' thought in the field of Islamic education has not only had an impact at the conceptual level, but also seen in its implementation in modern pesantren educational institutions in Indonesia. Many of the holistic and innovative principles he proposes have been applied successfully, helping to shape Islamic education that fits the demands of the times and the needs of the Indonesian people. The goal of Islamic education is to create Muslim individuals who are strong in faith, have noble character, are knowledgeable, and have practical world skills. Mahmud Yunus also championed an Islamic education curriculum that unites religious knowledge and general science, as well as integrated Arabic language teaching. His thinking influenced modern pesantren educational institutions in Indonesia in developing holistic and modern Islamic education in Indonesia.